Socialna demokracija na slovenskem Štajerskem in problem nacionalne razdelitve - Rozman, Franc (Zgodovinski časopis, 1986)
On the basis of contemporary newspaper reports the author describes the struggle of the Yugoslav Socio-Democratic Party (JSDS) for its organizations in Lower Styria, especially in Celje district. The Styrian regional organization offered opposition from 1896 till 1911, when the JSDS succeeded in organizing all its organizations in Celje district, but, however, not more northwards. The German organizations in Celje was left the possibility of belonging directly to Gradec. The programme of the Brno Congress referring to the exceeding of the crown-lands' borders in this field just couldn't begin to live.
Keywords: history; social democracy; socialna demokracija; zgodovina